Culinary Creations for the Development of MSMEs in Creating Traditional West Cikalong Foods and Drinks - Ana Wijandari; Samsul Arifin; Rofiq Noorman Haryadi; Destiana Kumala (Pasundan Community Service Development, 2023)
This article explores the pivotal role of traditional culinary arts in fostering the development of Micro, Small, and Medium Enterprises (MSMEs) in West Cikalong. Emphasizing community involvement, it delves into how local food and drink specialties serve as a catalyst for economic growth and social enrichment. The study highlights the diverse culinary heritage of West Cikalong, underscoring the potential of indigenous food and drinks for commercial success. It examines the initiatives aimed at skill development, focusing on traditional cooking techniques and recipes, and how these bolster MSME growth. The article addresses the challenges in preserving authenticity and competing in the market, while recognizing opportunities for innovation and expansion. Incorporating case studies, it showcases successful local MSMEs that have made significant community impacts through culinary endeavors. Furthermore, the role of culinary tourism in enhancing local economic stability and MSME development is discussed. This study underscores the synergy between culinary heritage and economic development, advocating for the integration of traditional culinary practices into MSME strategies as a means for community empowerment and sustainable development in West Cikalong.